Efektifitas Pelatihan Kebersyukuran Untuk Meningkatkan Kualitas Hidup pada Pasien Hipertensi - Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2020)
Gratitude training is one of the Islamic intervention that is able to improve quality of life in hypertension patients. It applied quasy experimental design with pretest-posttest with control group design. Participants consist of 23 hypertension patients and at least diagnosed for 1 year. The result showed that gratitude training able to improved quality of life in hypertension patients. This indicated by increasing the score of quality of life in experiment group (MD = -18.833, p = 0.000 on pretest to posttest; MD = -28.417, p = 0.000 on pretest to follow up). MD’s negative value indicates that the mean score of the quality of life during posttest and follow up was higher than the mean score during pretest. It means gratitude training can be used to improve quality of life in hypertension patients. So it can also a companion to medical intervention.